INFLUENCE OF THE SMALL HYDROPOWER STATIONS ON THE HYDROLOGIC PROCESSES IN THE SERET RIVER (LEFT TRIBUTARY OF THE DNISTER RIVER) - Olha Pylypovych; Andrii Mykhnovych; Yuriy Andreychuk; Uliana Morozovs’ka (Environmental Problems)
Sources of the Seret River are locatednear Ratyshchi village in Ternopil region. The river has the length of 248 km, the catchment area is about 3,900 km2. During the last 15 years seven small hydropower stations (SHPS) have been constructed in the Seret riverbed (Zahidhydroenergo, Velykohaivs’ka, Lux-2, Yanivs’ka, Chortkivs’ka, Bilche-Zolotets’ka, Bilche-Zolotets’ka-2, and Kasperivs’ka). Since all the SHPS are situated in the Seret riverbed and have a dam which decelerate water flow velocity, they influence the water runoff, sediments runoff, and water quality. After their building the cases of flooding of villages, overgrowing of the river bed reservoirs by algae plants became more often, and the long-term dynamics of the water and sediments runoff changed.To assess the water and sediments runoff changes in the catchment and to ascertain correlation between these changes and the SHPS the monitoring data sets of the Hydro-Meteorological Survey of Ukraine and the Carpathian Hydrological Observatory were analyzed. Recently the observations on the water runoff are implemented at two gauging stations: VelykaBerezovytsiavillage and Chortkivcity. The sediments runoff data are collected by the Chortkiv gauging station. The assessment of the water and sediments runoff changes in the Seret River in the period 1948–2022 and ascertaining of the role of water regulating by dams and reservoirs of small hydropower stations in the riverbed have been carried out. We also carried out a comparison of the sediments runoff module for the Seret River and the neighbouring Koropets River.